Analisis Penyusunan dan Pelaksanaan Anggaran Pada BAPPEDA Aceh Barat Daya - Munawarah, Munawarah; Darmayanti, Cici (Jurnal Ilmiah Manajemen Kesatuan, 2024)
A budget is a written plan that describes the estimated income and expenditure planned by an individual, organization, or government entity within a certain period of time. This research aims to determine the preparation and implementation of the budget at the Regional Development Planning Agency of Southwest Aceh Regency. This is useful for the development of the Southwest Aceh region in identifying the effectiveness of the budget preparation and implementation process by BAPPEDA to support regional development planning. The type of research used in this research is descriptive qualitative research. The subject of this research is the finance section of Development Planning Agency at Sub-National Level (Badan Perencanaan Pembangunan Daerah/BAPPEDA) Aceh Barat Daya. The data sources used in this research are primary data and secondary data. Primary data in this research comes from observations made by researchers and direct interviews with several heads of fields, namely the Head of Reports and Programs, the Head of P2EP3 and the Head of PPKAPM. The results of the research show that the preparation of the budget at BAPPEDA Aceh Barat Daya has been carried out very well and the implementation of the BAPPEDA Aceh Barat Daya budget for the 2022 Fiscal Year has been efficient.